STESYS software for computer-assisted stereology - Karen, P; Kubínová, L; Krekule, I (Physiological research, 1998)
A software system STESYS for interactive and flexible generation of stereological test systems is described. STESYS enables to implement many of the recent unbiased stereological methods applied to biomedical research and clinical diagnosis by using a simple personal computer. Advantages of the STESYS software are illustrated by several examples of stereological measurements for estimating the number, total and mean cross-sectional area, volume and surface area.
Keywords: Image Processing, Computer-Assisted; mikropočítače; placenta; matematika; software; Capillaries; Placenta; Microcomputers; Software; Mathematics; axony; kapiláry; počítačové zpracování obrazu; Axons